2022
DOI: 10.3389/fgene.2022.1034921
|View full text |Cite
|
Sign up to set email alerts
|

Pangenome-wide analysis of cyclic nucleotide-gated channel (CNGC) gene family in citrus Spp. Revealed their intraspecies diversity and potential roles in abiotic stress tolerance

Abstract: Cyclic nucleotide-gated channels (CNGC) gene family has been found to be involved in physiological processes including signaling pathways, environmental stresses, plant growth, and development. This gene family of non-selective cation channels is known to regulate the uptake of calcium and is reported in several plant species. The pangenome-wide studies enable researchers to understand the genetic diversity comprehensively; as a comparative analysis of multiple plant species or member of a species at once help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…We identified 3,515 and 2,262 sequences uniquely present in XsoG11 by comparing this assembly with Xsv2 and WF18 genomes, respectively, in which 1,005 sequences are present in the XsoG11 genome but missing in both Xsv2 and WF18 genomes ( Figure 3B ). In addition, we further performed the pan-genome wide analysis of gene families ( Zia et al., 2022 ). The pangenome-wide gene family clustering analysis revealed that these three genomes shared 11,750 core orthologous clusters, whereas at least one genome (but less than three) shared 8,844 dispensable orthologous clusters, with 677 XsoG11-specific dispensable orthologous clusters ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 3,515 and 2,262 sequences uniquely present in XsoG11 by comparing this assembly with Xsv2 and WF18 genomes, respectively, in which 1,005 sequences are present in the XsoG11 genome but missing in both Xsv2 and WF18 genomes ( Figure 3B ). In addition, we further performed the pan-genome wide analysis of gene families ( Zia et al., 2022 ). The pangenome-wide gene family clustering analysis revealed that these three genomes shared 11,750 core orthologous clusters, whereas at least one genome (but less than three) shared 8,844 dispensable orthologous clusters, with 677 XsoG11-specific dispensable orthologous clusters ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…LRR proteins recognize pathogen effectors and trigger innate immunity in plants [ 60 ]. Calcium, which acts as a secondary messenger in plants and its sensors are important in abiotic and biotic stress resistance [ 61 ]. CDPKs mediate innate immunity in plants by regulating oxidative burst and hormone signal transduction in response to plant pathogens [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…To predict the selection pressure on the duplicated genes, Ka/Ks values were calculated using DnaSP v.6 software ( Le et al, 2011 ; Rozas et al, 2017 ). Based on whether the Ka/Ks ratio was greater than, equal to, or less than one, purifying, neutral, or positive selection was inferred ( Zia et al, 2022 ). Additionally, the divergence time for the duplicated gene pairs was estimated using the formula “t = Ks/2λ×10 –6 ″ in million years (Mya), where the λ value is 1.5 × 10 −8 for dicots ( Fatima et al, 2023 ; Sadaqat et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%